Application of the Hollow Sprint Method to the Results of the 100 Meter Run for Class X Students at SMAN 9 Seluma - Nozi Fitrawan; Feby Elra Perdima; Supriyanto Supriyanto (Penerbit Jurnal Indonesia, 2023)
The purpose of this study was to determine the effect of the application of the hollow sprint method on the results of the 100 meter run in class X students at SMAN 9 Seluma. In this study, the research method used is the experimental method. The subjects of this study were students of class XA at ​​SMAN 9 Seluma as many as 32 students. Data collection techniques used in the research are test, observation and documentation methods. Analysis of the data used in quantitative research using the 100 meter running assessment guidelines. The conclusion of this research is the application of the effect of the application of the hollow sprint method has a significant influence on the results of the student's 100 meter run with the results of the t-test in the class studied both in the implementation of observations and the application of the hollow sprint method. The results of the observations obtained the value of t count or t count 11.41 > t table 1.695. And after the implementation of the holow sprint method, the results of the t test are t count or t count 16.95 > t table 1.695, so that the hypothesis which states that the application of the hollow sprint method has an effect on the results of the 100 meter run in class XA SMAN 9 Seluma is acceptable. the truth.